An Act in Addition to an Act, entitled “An Act to Provide for the Proof of Fire Arms, Manufactured within this Commonwealth,” 1814 Mass. Acts 464, ch. 192, § 2 - (:unkn) unknown (General Publisher, 1814)
Requiring all musket barrels and pistol barrels, manufactured within this Commonwealth to be proved by the person appointed according to the provisions of an act . . . with a charge of powder equal in weight to the ball which fits the bore of the barrel to be proved.
--
Keywords: MANUFACTURE ONLY